THE EFFECT OF PROBLEM-BASED LEARNING MODEL ON STUDENTS' MATHEMATICAL COMPUTATIONAL THINKING SKILLS - Maulidya Asrianti; Fibri Rakhmawati (USN Kolaka, 2024)
This study aims to determine the effect of Problem Based Learning model on students' mathematical computational thinking ability. The sample of this study involved 8th grade students of Madrasah Tsanawiyah (MTs) Hifzhil Qur'an Yayasan Islamic Centre Sumatera Utara in the 2023-2024 school year totaling 53 people. The sampling technique used was cluster random sampling so that researchers had 2 class groups, namely class 8-3 as the experimental class and class 8-4 as the control class. The method used is quantitative experimentation with a research design in the form of True Experimental Design in the form of Post-test-Only Control Design. The analysis of this study used Independent Sample t Test and obtained a sig value. <0,001. Thus H0 is rejected and Ha is accepted, meaning that there is a significant effect of using Problem Based Learning model on students' mathematical computational thinking skills.